Project method as a new personality-oriented technology of teaching foreign languages in technical universities - Voronova, Ye. M.; Воронова, Єлізавета Михайлівна; Воронова, Елизавета Михайловна (Харківський національний автомобільно-дорожній університет, 2020)
The article emphasizes that one of the most organic and effective forms of independent learning by students while learning a foreign language is the project method. The novelty of the project method as a relatively new method of teaching foreign languages, which is a personality-oriented technology, is shown. The project method is now very actual because, as a relatively new method in teaching foreign languages, it actively involves students in various practical activities and allows them to develop their creative and individual abilities. The project method is one of the methods of developing communicative competence in the study of English by students of technical universities. The use of the method of educational projects in pedagogical work is determined by the need to form a person of the XXI century, a person of a new era, when the determining factors in the development of society are human intelligence and information. It is shown that the project method is one of the methods of developing communicative competence in learning English by students of technical universities. Project method as a new personality  oriented technology of teaching foreign languages  in technical universities. The main purpose of the project method is to provide students with the opportunity to acquire independently knowledge in the process of solving practical problems or problems that require the integration of knowledge from different subject areas. The role of the teacher is a coordinator, an expert, a certain source of additional information. Unlike other technologies, the project method makes it possible to involve students in real communication, full of foreign language contacts, it is a method of achieving a specific (methodical) goal by researching the problem and getting a really practical result, namely the development of communicative competence of future professionals. The article shows the differences between teaching by traditional methods and when learning with the help of the project method. The project method is an alternative to the traditional approach to education, which is based mainly on the acquisition of ready knowledge and their perception. The project methodology shifts the emphasis from different types of exercises to active mental activity of students who need skillful mastery of certain language tools.
Проектний метод як нова орієнтована технологія навчання іноземних мов в технічних університетів.
Проектный метод как новая лично-ориентированная технология обучения иностранным языкам в технических вузах
Keywords: acquiring knowledge; method; novelty; personality -oriented; technology communicative competence; придбання знань; методика; новизна; особистісно-орієнтованість; комунікативна компетентність; приобретение знаний; личностно-ориентированность; коммуникативная компетентность; 372.881.111. 1; 10.30977/BUL.2219-5548.2020.91.0.226